Market Incentives for Safe Commercial Airline Operation - Borenstein, Severin; Zimmerman, Martin B. (American Economic Review, 1988)
Airlines are insured against most direct costs of an accident, but they cannot insure against demand loss. Our estimation of deviations from expected demand following accidents finds little or no effect prior to airline deregulation and weak indication of a response to recent crashes. These results are consistent with the changes in an airline's equity value following an accident, which are statistically significant, but quite small relative to the total social cost of the accident.